2019
DOI: 10.1053/j.tcam.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Effects on the Corneoconjunctival Microflora in a Population of Persian Cats in Iran

Abstract: This study was performed to determine the normal seasonal aerobic and an-aerobic corneoconjunctival bacterial flora in cats. Thirty eyes of 15 clinically normal client-owned Persian cats were evaluated. All cats lived in a similar indoor/outdoor home environment being fed the same diet for the entire year. The cats did not receive any medications and were found to be clinically healthy 1 week prior to each microbial sampling. The cats were not exposed to other cats during the study period. Microbial samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Seasonal influences and effects of season on the conjunctiva flora have been reported in humans, dogs, cats, and horses 23–27 . Aftab et al reported a lower number of positive bacterial cultures and number of gram‐negative bacteria isolates in the cold seasons in a population of Persian cats 25 . Results published by Büttner et al confirm that the season had a significant effect on the frequency of isolation 26 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Seasonal influences and effects of season on the conjunctiva flora have been reported in humans, dogs, cats, and horses 23–27 . Aftab et al reported a lower number of positive bacterial cultures and number of gram‐negative bacteria isolates in the cold seasons in a population of Persian cats 25 . Results published by Büttner et al confirm that the season had a significant effect on the frequency of isolation 26 .…”
Section: Discussionmentioning
confidence: 91%
“…Although similar methods were used to detect bacterial microorganisms, these findings should be interpreted with caution as many of the differences exist in climate between Canada, where the cats from the Shewen study were, and Iran. Seasonal influences and effects of season on the conjunctiva flora have been reported in humans, dogs, cats, and horses 23–27 . Aftab et al reported a lower number of positive bacterial cultures and number of gram‐negative bacteria isolates in the cold seasons in a population of Persian cats 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Espínolaz & Lilenbaum (1996) emphasize the importance of the species S. felis, although they indicate a significant prevalence of S. epidermidis (45.7%), S. simulans (23.9%), S. auricularis (17%) and S. saprophyticus (6.5%) ). Aftab et al (2019) note also the high presence in the conjunctival sac of S. pyogenes (18.9%) and Escherichia coli (11.5%). A significant increase in the prevalence among cats resistant to antibacterial agents of pathogenic Staphylococcus species, in particular S. aureus, has been demonstrated (Lane et al, 2018).…”
Section: Introductionmentioning
confidence: 82%
“…According to Aftab et al (2019), conjunctivitis is not characterized by seasonality against the background of predominance of gram-positive bacteria -S. epidermidis (43.2%), β-hemolytic streptococcus (18.9%), S. aureus (17.9%) and E. coli (11.5%). At the same time, we found that their registration in the cold season was significantly higher, although gram-positive microorganisms were most often also isolated.…”
Section: Discussionmentioning
confidence: 99%
“…In cats, the number of Gram‐negative bacteria was reported to be increased during cold seasons (Aftab et al., 2019 ). In clinically normal dogs, the number of positive bacterial cultures was different during cold and warm seasons (Wang et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%